A quadratic equation in the variable x is an equation of the form ax^{2} + bx + c = 0, where a, b, c are real numbers and a ≠ 0 is called the standard form of a quadratic equation.
Example 1: Check whether the following are quadratic equations
i) (x + 1)^{2} = 2(x − 3)
⇒ (x + 1)^{2} = x^{2} + 2x + 1
∵ (a + b)^{2} = a^{2} + 2ab + b^{2}
⇒ x^{2} + 2x + 1 = 2(x − 3)
⇒ x^{2} + 2x + 1 = 2x − 6
⇒ x^{2} + 2x + 1 − 2x + 6 = 0
⇒ x^{2} + 2x − 2x + 6 + 1 = 0
x^{2} + 7 = 0
The above equation is a quadratic equation, where the coefficient of x is zero, i.e. b = 0
ii) x(x + 1)(x + 8) = (x + 2)(x − 2)
LHS
⇒ x(x + 1)(x + 8)
⇒ x(x^{2} + 8x + x + 8)
⇒ x(x^{2} + 9x + 8)
⇒ x^{3} + 9x^{2} + 8x
RHS
(x + 2)(x − 2)
⇒ x^{2} − 4
∵ (a + b)(a − b) = a^{2} − b^{2}
Now, x^{3} + 9x^{2} + 8x = x2 − 4
⇒ x^{3} + 9x^{2} − x^{2} + 8x + 4 = 0
x^{3} + 8x^{2} + 8x + 4 = 0
It is not a quadratic equation as it is an equation of degree 3.
iii) (x − 2)^{2 }+ 1 = 2x − 3
LHS
(x − 2)^{2} + 1 = x^{2} − 2x + 4 + 1
∵ (a − b)^{2} = a^{2} − 2ab + b^{2}
= x^{2} − 2x + 5
RHS
2x − 3
⇒ x^{2} − 2x + 5 = 2x − 3
⇒ x^{2} − 2x − 2x + 5 + 3 = 0
⇒ x^{2} − 4x + 8 = 0
The above equation is quadratic as it is of the form,
ax^{2} + bx + c = 0
Example 2: The product of two consecutive positive integers is 420. Form the equation satisfying this scenario.
Let the two consecutive positive integers be x and x + 1 Product of the two consecutive integers= x(x + 1) = 420
⇒ x^{2} + x = 420
⇒ x^{2 }+ x − 420 = 0
x^{2} + x − 420 = 0, is the required quadratic equation and the two integers satisfy this quadratic equation.
A real number α is called a root of the quadratic equation x^{2 }+bx + c = 0 , a ≠ 0 if aα^{2} + bα + c = 0
We say that x = α is a solution of the quadratic equation.
Example: x^{2} − 2x − 3 = 0
If we put x = −1 in the LHS of the above equation we get,
(−1)^{2} − 2(−1) − 3
1 + 2 − 3 = 0
Thus x = −1 is a solution of the equation x^{2} − 2x − 3 = 0.
To find the roots of the quadratic equations we follow these steps.
Example 3: Find the roots of the equation x^{2} − 3x − 10 = 0
The given equation is x^{2} − 3x − 10 = 0.
Here a = 1, b = −3 and c = −10
1) Find the product of a and c .
Here, the product of a and c= 10 → (ac) is negative
2) Write the factors of this product (ac) such that the sum of the two factors is equal to b.
∴ ac = m × n and m + n = b
Factors of 10 = 2×5
Let m = −5 and n = 2 → (ac=10)
We write the given equation as,
x^{2} − 5x + 2x − 10 = 0
x(x − 5) + 2(x − 5) = 0
x − 5 x + 2 = 0
Equate each factor to zero to get the roots of the equation.
x − 5 = 0 and x + 2 = 0
x = 5, −2
Therefore, 5 and 2 are the roots of the equation x^{2} − 3x − 10 = 0
Example 4: Solve the following quadratic equation by factorisation method.
i) 4√3x^{2} + 5x − 2√3 = 0
The given equation is 4√3x^{2} + 5x − 2√3 = 0
Here, a = 4√3 , b = 5 and c = −2√3
The product of a and c
= 4√3 × (−2√3 )
= −8 × 3
= −24
Factors of 24 = 3×8 and 8 + (−3) = 5
The factors of the equation are 8, − 3
So, the given equation can be written as,
4√3x^{2} + (8 − 3)x − 2√3 = 0
⇒ 4 √3x^{2} + 8x − 3x − 2√3 = 0
⇒ 4x( √3x + 2) −√3 (√3 x + 2) = 0
⇒ (4x − √3 )(√3x + 2) = 0
Equating each factor to zero we get,
(4x −√3 )=0 and (√3x + 2) = 0
The roots of the equation
The given equation is
Multiplying the above equation by x^{2 }we get,
Here, a = 2, b = −5 and c = 2
The product of a and c = 2 × 2 = 4
The factors of 4 = 4 × 1 and 4 + 1 = 5
2x^{2} − (4 + 1)x + 2 = 0
⇒ 2x^{2} − 4x − 1x + 2 = 0
2x(x − 2) − (x − 2) = 0
(2x − 1)(x − 2) = 0
Equating each factor to zero we get,
(2x − 1) = 0 and (x − 2) = 0
x = 1/2 and x = 2
The roots of equation 2x^{2 }− 5x + 2 = 0 are 1/2 and 2
Example 5: The altitude of a rightangled triangle is 7 cm less than its base. If the hypotenuse is 13 cm long, then find the other two sides.
Let the length of the base be x cm, then altitude = x − 7 cm
Hypotenuse = 13 cm
We know, H^{2} = P^{2} + B^{2}
132 = (x − 7)^{2} + x^{2}
⇒ 169 = x^{2} − 14x + 49 + x^{2}
⇒ x^{2} − 14x + 49 + x^{2} = 169
⇒ 2x^{2} − 14x + 49 − 169 = 0
⇒ 2x^{2} − 14x − 120 = 0
Dividing the above equation by 2 we get,
x^{2} − 7x − 60 = 0
Here, a = 1, b = −7 and c = −60
The product of a and c = 1 × (−60) = −60
The factors of 60 = 5 × 12 and −12 + 5 = 7
The given equation can be written as,
x^{2} − 12x + 5x − 60 = 0
x(x − 12) + 5(x − 12) = 0
⇒ (x + 5)(x − 12) = 0
Equating each factor to zero we get,
(x + 5) = 0 and (x − 12) = 0
⇒ x = −5 and x = 12
The length of the base cannot be negative.
Therefore, Base = 12 cm
Altitude = x − 7 cm = 12 − 7 = 5 cm, Hypotenuse = 13 cm
The roots of the quadratic equation ax^{2} + bx + c = 0 are given by
Where D = √b^{2} − 4ac is called the discriminant.
This formula is known as the Quadratic Formula.
The nature of the roots depends upon the value of Discriminant, D.
Example 6: Find the roots of the equation,
The given equation is
Squaring both sides of the equation we get,
Here, a = 4, b = −37 and c = 40
Substituting the value of a, b and c in the quadratic formula
Taking +ve sign first,
Taking ve we get,
The roots of the given equation are 8 and 5/4.
Example 7: Find the numerical difference of the roots of the equation x^{2} − 7x − 30 = 0
The given quadratic equation is x^{2 }− 7x − 30 = 0
Here a = 1, b = −7 and c = −30
Substituting the value of a, b and c in the quadratic formula
Taking +ve sign first,
Taking ve we get,
The two roots are 10 and 3
The difference of the roots= 10 − (−3) = 10 + 3 = 13
Example 8: Find the discriminant of the quadratic equation x^{2} −4x − 5 = 0
The given quadratic equation is x^{2} − 4x − 5 = 0.
On comparing with ax^{2} + bx + c = 0 we get,
a = 1,b = −4, and c = −5
Example 9: Find the value of p, so that the quadratic equation px(x − 2) + 9 = 0 has equal roots.
The given quadratic equation is px(x − 2) + 9 = 0
px^{2} − 2px + 9 = 0
Now comparing with ax^{2} + bx + c = 0 we get,
a = p, b = −2p and c = 9
The given quadratic equation will have equal roots if D = 0
p = 0 and p − 9 = 0 ⇒ p = 9
p = 0 and p = 9
The value of p cannot be zero as the coefficient of x, (−2p) will become zero.
Therefore, we take the value of p = 9.
Example 10: If x = −1 is a root of the quadratic equations 2x^{2} +px + 5 = 0 and the quadratic equation p(x^{2} + x) + k = 0 has equal roots, then find the value of k.
The given quadratic equation is 2x^{2} + px + 5 = 0. If x = −1 is the root of the equation then,
2(−1)2 + p(−1) + 5 = 0
2 − p + 5 = 0
⇒ −p = −7
p = 7
Putting the value of p in the equation p(x^{2} + x) + k = 0,
7(x^{2} + x) + k = 0
⇒ 7x^{2} + 7x + k = 0
Now comparing with ax^{2} + bx + c = 0 we get,
a = 7, b = 7 and c = k
The given quadratic equation will have equal roots if D = 0
Therefore, the value of k is 7/4.
If we have to find the solution of a quadratic equation by completing the square, we follow the steps given below.
The complete square is,
Example 11: Find the roots of the following quadratic equations by the method of completing the square:
i) 2x^{2} − 7x + 3 = 0
The given quadratic equation is 2x^{2} − 7x + 3 = 0
The coefficient of x2 is not 1, so we divide the whole equation by 2.
Now move 3/2 to RHS
Adding (7/4)^{2 }to both sides we get,
Taking square root of both sides we get,
The roots of the equation are 3 and 1/2
ii) 4x^{2 }+ 4√3x + 3 = 0
Dividing the whole equation by 4, so that the coefficient of x^{2} is 1.
Shifting 3/4 to RHS
Adding to both sides we get,
Taking the square root of both sides
The roots of the given equation are
Example 12: Solve the quadratic equation
x^{2} − (√5 + 1)x + √5 = 0 by completing the square method.
The given quadratic equation is, x^{2} − (√5 + 1)x = −√5 = 0
Shifting √5 to RHS we get,
x^{2} − (√5 + 1)x = −√5
Adding to both sides we get,
Taking +ve sign first
Taking –ve sign
The roots of the given equation are √5 and 1
120 videos463 docs105 tests

1. What is a quadratic equation? 
2. How can we solve a quadratic equation by factorisation? 
3. What is the nature of roots in a quadratic equation? 
4. How can we solve a quadratic equation by completing the square? 
5. Why was the method of solving quadratic equations by completing the square deleted from the NCERT textbook? 
120 videos463 docs105 tests


Explore Courses for Class 10 exam
